Evaluation of enteric methane production in dairy cows fed Acacia mearnsii - Mhlongo, Lindokuhle C; Nsahlai, Ignatius V (Journal of Advanced Veterinary and Animal Research, 2025)
Objectives: We investigated the effect of different incorporations of Acacia mearnsii forage (AM) in maize silage or A. mearnsii tannin extract (AME) in pellets on dairy rumen CH4 . Materials and Methods: Using a completely randomized design per experiment, 24 crossbred Holstein–Friesian and Jersey dairy cows per experiment were divided into groups (n = 6 cows per experiment). Dairy cows were fed pellets with 0% (0PEL), 0.75% (0.75PEL), 1.5% (1.5PEL), or 3.0% (3PEL) of AME (Experiment 1). Furthermore, dairy cows were fed 0% (0AM), 5% (5AM), 15% (15AM), or 25% (25AM) of AM in maize silage (Experiment 2). Data sampling period (21 days) of ruminal CH4 and nitrogen (N2 ), carbon dioxide (CO2 ), and hydrogen (H2 ) gases (% vol) was conducted after the adaptation period (14 days) for each experiment. Results: Enteric CH4 was not affected by AME inclusion, but AM inclusions affected CH4, except for CH4 (% vol per cow per day). The inclusions of 25AM decreased CH4 per nutrient intake (kg/ day), such as dry matter (DM), organic matter (OM), crude protein, acid detergent fiber (ADF), and neutral detergent fiber (NDF). In addition, there was a linear and quadratic AM inclusion effect on CH4 per intake of nutrients, including DM, NDF, ADF, and OM. Conclusion: Enteric CH4 was not affected by AME but was decreased by AM in dairy cows. J. Adv. Vet. Anim. Res., 12(3): 1030–1036, September 2025 http://doi.org/10.5455/javar.2025.l962